Complex admixtures for high-strength concrete - Skripkiūnas, Gintautas; Rudžionis, Žymantas; Vaitkevičius, Vitoldas (Journal of Civil Engineering and Management, 2002)
The influence of naphthalene formaldehyde superplasticizers (NFS), lignosulfonate plasticizers (LSP) and silica fume on cement paste properties and complex usage of these admixtures for high-strength concrete production are investigated in this research. These admixtures influence the cement hydration products morphology and properties of hardened cement paste. The degree of cement hydration and Ca(OH)2 content in hardened cement paste were determined for analysis of cement hydration process with admixtures. Mechanical properties and porosity of hardened cement paste with the admixtures were tested. Optimal dosages of plasticizing admixtures and silica fume were estimated and the most efficient method of silica fume adding to concrete mixture was proposed. The results of investigation have been used for high-strength concrete production.Frist Published Online: 30 Jul 2012